Overnight orthokeratology - Bullimore, Mark A.; Johnson, Leah A. (Contact lens & anterior eye, 2020)
Overnight orthokeratology lenses are approved in countries all over the world for the temporary reduction in myopia, and recently, one lens design has received regulatory approval for myopia control in Europe. The modern orthokeratology lens has a substantial history from its origins of attempting to flatten the corneal curvature with a spherical rigid contact lens to sophisticated gas permeable lenses, designed to reshape the cornea. These lenses are predominantly prescribed for children to slow myopia progression and limit axial elongation of the eye. This article reviews the peer-reviewed literature on the efficacy of orthokeratology for myopia control, sustainability after treatment is discontinued, and the safety concerns of overnight contact lens wear. Future avenues of research are discussed.